Method for synthesizing trans-4-(trans-4'-alkylcyclohexyl)cyclohexylethylene liquid crystal monomer - JU NIJUAN; SHEN NING; BAO BIN; FENG XIAOQIONG; DUAN YINGCHUN; DONG JINMENG; HOU XIUZE; GAO RENXIAO (2018)
The invention relates to a method for synthesizing a trans-4-(trans-4'-alkylcyclohexyl)cyclohexylethylene liquid crystal. A desired product is prepared from trans-4-(trans-4'-alkylcyclohexyl)cyclohexylethanone as a raw material through alpha-bromination, reduction, intramolecular etherification, ring-opening bromination and debromination alkene formation. The method has the advantages of easy availability of raw materials, high yield of various steps, easy purification of products and low cost. The entire route uses cheap toluene, ethanol and methanol as solvents, prevents the problems of lowatomic utilization and many by-products of the wittig reaction and prevents the environmental problems produced by highly concentrated tetrahydrofuran wastewater. Environmental friendliness is one ofthe highlights of the route. 本发明涉及种反-4-(反-4'-烷基环己基)环己基乙烯类液晶的合成方法。采用反-4-(反-4'-烷基环己基)环己基乙酮为原料，经过α-溴代、还原、分子内醚化、开环溴代、脱溴形成烯的方法，得到目标产物。本发明具有原料易得、各步收率高、产物易于纯化、成本低的优点。整条路线采用廉价的甲苯、乙醇、甲醇等为溶剂，避免了wittig反应的低原子利用率、副产物多的问题，避免高浓四氢呋喃废水的产生的环境问题